2009
DOI: 10.1148/radiol.2531082113
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: Contribution of 3.0-T Pelvic MR Imaging in Preoperative Assessment—Initial Results

Abstract: MR imaging of the pelvis at 3.0 T is accurate in the diagnosis and staging of deep endometriosis for the preoperative assessment of patients clinically suspected of having endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 28 publications
3
72
0
7
Order By: Relevance
“…Although transvaginal US is considered to be the primary imaging modality for diagnosis of endometriosis, the role of MRI in patients with pelvic pain symptoms has been expanding steadily over the past years (5)(6)(7)(8). Currently, the state-of-the-art imaging protocol for the evaluation of endometriosis includes T2-and fat suppressed T1-weighted sequences in various different imaging planes (7)(8)(9). This provides consistent information on the extent, severity, as well as the stage of hemorrhagic components of endometriosis, especially in DIE.…”
Section: Deep Infiltrating Pelvic Endometriosis (Die)mentioning
confidence: 99%
“…Although transvaginal US is considered to be the primary imaging modality for diagnosis of endometriosis, the role of MRI in patients with pelvic pain symptoms has been expanding steadily over the past years (5)(6)(7)(8). Currently, the state-of-the-art imaging protocol for the evaluation of endometriosis includes T2-and fat suppressed T1-weighted sequences in various different imaging planes (7)(8)(9). This provides consistent information on the extent, severity, as well as the stage of hemorrhagic components of endometriosis, especially in DIE.…”
Section: Deep Infiltrating Pelvic Endometriosis (Die)mentioning
confidence: 99%
“…It presents a high specificity in diagnosing endometriomas (98%) [25], owing to its ability to characterise haemorrhage. 'Shading' is a specific sign of endometrioma; it is caused by old blood products, which contain extremely high iron and protein concentrations.…”
Section: Endometriomamentioning
confidence: 99%
“…Pelvic 3T MRI guarantees a high spatial and contrast resolution, providing accurate information about endometriosis implants and a good pre-surgical mapping of lesions involving bowels, serosal surface of the bladder, and the utero-sacral ligaments [25,62]. Manganaro et al [62] reported 3T MRI mean sensitivity, specificity, positive predictive value and negative predictive value of 93%, 75%, 93%, 75%, respectively, in diagnosing DIE of the posterior compartment.…”
Section: Deep Infiltrating Endometriosis Of the Posterior-lateral Commentioning
confidence: 99%
“…Recto-sigmoid endometriosis may produce nonspecific symptoms such as diarrhea, rectal bleeding, and abdominal colic-like pain. This condition may require open surgery, and when the colon serosa is involved, meticulous dissection is required (3,4). Therefore, accurate preoperative imaging of recto-sigmoid involvement is important.…”
mentioning
confidence: 99%
“…The ''tenderness-guided'' TVUS (tg-TVUS) technique has shown promising results in the detection of DIE (7). MRI enables precise mapping of the nodules of endometriosis and is accepted as a valid imaging technique for evaluation of DIE before surgery (3,(8)(9)(10). However, the diagnostic value of the different signal intensities (hyper/ hypo/iso) shown by a nodule of endometriosis is still controversial.…”
mentioning
confidence: 99%